Democracy, pluralism, and conflict - Karna, M. N. (Mahendra Narain); North Eastern Hill University. Department of Sociology (Jaipur : Rawat Publications, 2006)
Contributed articles presented at a national seminar organized by Department of Sociol., North-Eastern Hill University, Shillong, May 2002.
Includes bibliographical references and index.
Keywords: DEMOCRACY -- INDIA; MULTICULTURALISM -- INDIA; CULTURAL PLURALISM -- INDIA; INDIA -- POLITICS AND GOVERNMENT